An Exploration of Tourists’ Perceptions of a Rural Mountain Bike Event - Brianna L. Newland; Martin Robertson (Journal of Applied Sports Management, 2018)
The natural attributes of rural locations are well suited to sport event tourism and can play a significant role in strategic tourism development in new markets. The purpose of the study was to explore consumer perceptions of sport event tourism in rural locations, which is important for event managers and for those involved in rural tourism development. Data collected over two days at a mountain bike event in the rural highlands of Scotland explored the visitor awareness and perception of events in a rural location. Results indicates that attendee background does influence the perception of the impact a sport event has on a rural location. Subscribe to JASM
Keywords: rural sport tourism; active sport tourism; mountain bike events